2021
DOI: 10.1016/j.molmet.2021.101276
|View full text |Cite
|
Sign up to set email alerts
|

HSP60 reduction protects against diet-induced obesity by modulating energy metabolism in adipose tissue

Abstract: Objective Insulin regulates mitochondrial function, thereby propagating an efficient metabolism. Conversely, diabetes and insulin resistance are linked to mitochondrial dysfunction with a decreased expression of the mitochondrial chaperone HSP60. The aim of this investigation was to determine the effect of a reduced HSP60 expression on the development of obesity and insulin resistance. Methods Control and heterozygous whole-body HSP60 knockout (Hsp60 +/− … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 48 publications
2
5
0
Order By: Relevance
“…Hauffe et al demonstrated that decreased HSP-60 levels in mice result in beneficial changes in adipose tissue morphology, body weight, and insulin resistance [26]. We came to a similar conclusion in this study because of the elevated HSP-60 levels in the patient group and the relationship between this elevation and proteinuria and inflammatory markers.…”
Section: Discussionsupporting
confidence: 86%
“…Hauffe et al demonstrated that decreased HSP-60 levels in mice result in beneficial changes in adipose tissue morphology, body weight, and insulin resistance [26]. We came to a similar conclusion in this study because of the elevated HSP-60 levels in the patient group and the relationship between this elevation and proteinuria and inflammatory markers.…”
Section: Discussionsupporting
confidence: 86%
“…Eight-week-old Hsp60-Tg FVB mice fed with an HFD for 6 months had lower levels of indicators of metabolic disorders (which include overweight status, glucose intolerance, insulin resistance, hypertriglyceridaemia, increased adiposity and hepatic steatosis). Previous studies have shown that 4-week-old C57BL/6N mice deficient in ubiquitous HSP60 had less obesity and fat mass than control mice upon HFD feeding for 16 weeks [35], whereas mice with hypothalamus-specific HSP60 knockout were insulin resistant [8]. We, thus, speculated that the role of HSP60 in metabolic disease development may be tissue context-dependent, and that mice with different genetic backgrounds or ages may have differing energy demands or fat metabolism capacities.…”
Section: Discussionmentioning
confidence: 94%
“…HSP60 is a mitochondrial chaperone protein with anti-inflammatory effects, whose loss determines mitochondrial functionality impairment, a known abnormality at the basis of cardiac insulin resistance and diabetic cardiomyopathy. 113 …”
Section: Role Of Adipocyte-derived Evs In Ischemia/reperfusion Injury...mentioning
confidence: 99%